Water quality status in different aquatic environments in Thi- Qar province based on NSF-WQI - Afaq T. Farhood (مجلة علوم ذي قار, 2019)
The present study was conducted during the period Winter &Summer of 2016 in different aquatic environments in Thi-Qar province to determine water quality status based NSF-WQI and some Iraqi & international standards. Three stations were chosen e to achieve the study, (each station consist from two sites), station (1) Euphrates River, station (2) Al-Gharraf River, station (3) Al- Chibayish Marshes.       The study result water quality conditions have been classified as (medium